Bio-Based Materials and Biotechnologies for Eco-Efficient Construction - Torgal, Fernando Pacheco, editor 544911; Ivanov, Volodymyr, editor 651050; Tsang, Daniel C. W., editor 651051; ScienceDirect (Online service) 7722 (Oxford : Woodhead Publishing, 2020)
Bio-based Materials and Biotechnologies for Eco-efficient Construction fills a gap in the published literature, discussing bio-based materials and biotechnologies that are crucial for a more sustainable construction industry. With comprehensive coverage and contributions from leading experts in the field, the book includes sections on Bio-based materials and biotechnologies for infrastructure applications, Bio-based materials and biotechnologies for building energy efficiency, and other applications, such as using biotechnology to reduce indoor air pollution, for water treatment, and in soil decontamination. The book will be an essential reference resource for academic researchers, civil engineers, contractors working in construction works, postgraduate students and other professionals.